Pesan Dakwah Kh Masrzuki Mustamar Dalam program Kiswah TV9 - Muhammad Nawawi; Wahyu Ardiansyah; Abdul Rohim; Lailatul Wahyu Fitriani (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2021)
This research examines the da'wah messages contained in KH Marzuqi Mustamar's lecture in the kiswah program on TV9. The research method used in this study is the discourse analysis of the Teun A. Van Dijk model. Using a descriptive type of content analysis approach. The data collection technique used documentation in the form of videos from KH Marzuqi Mustamar's lectures, then observed in depth by researchers to get accurate results. This study produces conclusions that contain three elements of the message of da'wah, namely creed, sharia, and morality. Meanwhile, the message of sharia is to remind Muslims to continue to carry out religious orders, such as praying, fasting, zakat, and so on. The message of morality is how as Muslims should be able to refrain from acting